Self-organization in magnetics - L.V. Chirkova; K.T. Ermaganbetov; E.T. Arinova; A. Omirbek (Қарағанды университетінің хабаршысы. Физика сериясы)
Application of the basic principles of the theory of self-organization to processes in magnetics is shown in article. It is also shown that if ferromagnetic are under the influence of a temperature or magnetic field, they can be considered as open, non-equilibrium thermodynamic system. Such system consists of atoms, molecules, domains with the magnetic moments, and also temperature and magnetic fields which interact among themselves and environment. In article change of the linear sizes of domains upon transition through Curie's point is considered. In article change of magnetization of magnetics and magnetostriction deformation from a synergetic position is analysed.